A Survey: Restoration of Compressed Image - S Sujithra, M.; SugithaSugitha, N. (International Journal of Engineering and Technology, 2019)
In recent years, blocking artifacts are the one of the major problem faced by the image compression due to quantization bit constraints or inter-block correlation in decompression. The various methods used to remove the blocking artifacts are broadly classified as deblocking methods and estimation / learning based methods. Both the methods are further classified into filtering approach and restoration of transform coefficients, maximum of a posteriori, projection onto convex sets and sparse dictionary learning. All these image restoration techniques are applied to restore the compressed image by considering the compressed image as degraded image. This paper presents various techniques for restoring compressed image and thereby maintaining the perceptual quality of the image.Â Â Â